Heat suit training preserves the increased hemoglobin mass after altitude camp in elite cyclists - Rønnestad, B. R.; Odden, I.; Urianstad, T.; Hansen, J.; Mølmen, K. S.; Cardinale, D. A. (Medicine & Science in Sports & Exercise, 2025)
Purpose Altitude training is a common strategy used with the intent to increase hemoglobin mass (Hbmass) in athletes. However, if the Hbmass is increased during altitude camps, it seems to decline rapidly upon returning to sea level. This study aimed to examine the efficacy of three weekly heat training sessions over a 3.5-wk period after a 3-wk altitude camp on the maintenance of Hbmass in elite cyclists.